Bush Nippers: Evaluating the effectiveness of the Nipper education program in regional inland Victoria, Australia. (5th January 2022) - Calverley, Hannah L. M.; Birch, Rhiannon; Strugnell, Grace; Santiago, Allana C.; Baker, Shayne; Matthews, Bernadette L.
Abstract: Issue addressed: Internationally, inland waterways are identified as leading locations for drowning. 'Nippers' programs provide coastal lifesaving and water safety knowledge and skills to children aged 5‐14 years in Australia. However, a 49% increase in Victorian inland waterway drowning compared with the 10‐year average, necessitated adapting the Nippers water safety program to inland regions: Bush Nippers. Methods: Overall, 105 participants from two age groups (under 9 and under 12) were involved across three Bush Nippers programs delivered at river and/or pool locations in regional Victoria, Australia. Surveys and observations assessed participants' water safety knowledge and competencies, and used alongside interviews to obtain program feedback from parents, instructors and communities. Costs were compared to other aquatic programs to determine feasibility of replicating the program. Results: Significant increases in knowledge from pre to immediate posttest were recorded ( P < .05) and water competencies were high posttest. Communities were grateful for the regional program delivery and understood the necessity of learning lifesaving skills, particularly in open water environments. Costs were akin to other similar programs indicating program replicability and enhancing likelihood of uptake. Conclusions: Bush Nippers increased water safety knowledge in children and was well received by the community. Wider uptake of the program is encouraged to diversify aquatic education for regional Victorian children. So what?: Given the high regard and demand for the program, and importance of learning lifesaving skills, provision of a scalable lifesaving program in inland regions may address the drowning trend and improve aquatic participation.